Scalable free-standing polypyrrole films for wrist-band type flexible thermoelectric power generator. (1st June 2019) - Bharti, Meetu; Jha, P.; Singh, Ajay; Chauhan, A.K.; Misra, Shantanu; Yamazoe, Masato; Debnath, A.K.; Marumoto, Kazuhiro; Muthe, K.P.; Aswal, D.K.
Abstract: Highly flexible free-standing polypyrrole films were prepared by the interfacial chemical polymerization of pyrrole (in cyclohexane) using aqueous FeCl3 as an oxidant and p-toluene sulphonic acid (PTSA) as a dopant. Morphological characterization revealed the granular morphology of the synthesized films and also suggested a reduction in their thickness with the increase in PTSA concentration. The increase of the doping content in these polypyrrole films, also resulted in the enhancement of electrical conductivity from 4.8 S/cm to 162.7 S/cm without much affecting the Seebeck coefficient ∼4–8 μV/K. The combined results of X-ray photoelectron spectroscopy and Electron spin resonance spectroscopy (ESR) confirms the enhancement of doping content (N + /N content) i.e. formation of charge carriers such as polarons/bipolarons with the increase in PTSA concentration. The synergetic combination of high electrical conductivity along with moderate Seebeck coefficient in the doped free-standing PPy films resulted in the highest average power factor of ∼0.45 μW/mK 2 . A wrist-band type thermoelectric power generator was also designed by integrating seven number of free-standing PPy films to manifest their potential for practical thermoelectric applications. The fabricated device exhibited maximum open-circuit voltage and current respectively as 336 μV and ∼46 nA, for a temperature difference of 80 °C. The work reveals new avenues towards the development of wearable energy harvesting devices that can be possibly designed using free-standing PPy films. Graphical abstract: A wrist-band type flexible thermoelectric power generator was designed and developed using highly flexible free-standing polypyrrole films that were synthesized by the interfacial chemical polymerization method.Image 105 Highlights: Free-standing PPy films were prepared by the interfacial polymerization route. The electrical conductivity of films was tuned from 4.8 S/cm to 162.7 S/cm. The optimally doped films exhibited an average power factor of ∼0.45 μW/mK 2 . A wrist-band type wearable thermoelectric device was fabricated. The electrical output of the device was ∼336 μV/46 nA for Δ T of 80 °C.